The orchard keeper - McCarthy, Cormac, 1933-2023; Sala, Ed.; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2013)
In a small, remote community in rural Tennessee in the years between the two world wars, John Wesley Rattner, a young boy, and Marion Sylder, an outlaw and bootlegger who, unbeknownst to either of them, has killed the boy's father enact a drama that seems born of the land itself.
Compact disc.
Title from container.
In container (17 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Keywords: Community life -- Fiction; Tennessee, East -- Fiction; Psychological fiction; Audiobooks